A multicenter study of diet quality on birth weight and gestational age in infants of HIV‐infected women. Issue 4 (8th November 2016) - Miller, Tracie L.; Jacobson, Denise L.; Somarriba, Gabriel; Neri, Daniela; Kurtz‐Vraney, Joy; Graham, Patricia; Gillman, Matthew W.; Landy, David C.; Siminski, Suzanne; Butler, Laurie; Rich, Kenneth C.; Hendricks, Kristy; et al.
Abstract: We determined factors associated with diet quality and assessed the relationship between diet quality, birth weight, and gestational age in a prospective national multicenter cohort study. We evaluated diet quality with the Healthy Eating Index (HEI, scale 0–100) in the third trimester of pregnancy with three 24‐hr multiple‐pass dietary recalls in 266 HIV+ women enrolled in the Pediatric HIV/AIDS Cohort Study. Covariates included demographics, food security, pre‐pregnancy body mass index, HIV disease severity, substance use, and antiretroviral exposures. A two‐stage multivariate process using classification and regression trees (CART) followed by multiple regression described HEI tendencies, controlled possible confounding effects, and examined the association of HEI with birth weight and gestational age. To assess the stability of the CART solution, both the HEI 2005 and 2010 were evaluated. The mean HEI scores were 56.1 and 47.5 for the 2005 and 2010 HEI, respectively. The first‐stage CART analysis examined the relationship between HEI and covariates. Non‐US born versus US‐born mothers had higher HEI scores (15‐point difference, R 2 = 0.28). There was a secondary partition due to alcohol/cigarette/illicit drug usage (3.5‐point difference, R 2 = 0.03) among US‐born women. For the second‐stage CART adjusted multiple regression, birth weight z‐score was positively related to HEI 2005 and 2010 (partial r 's > 0.13, P 's ≤ 0.0398), but not gestational age ( r = 0.00). We conclude that diet quality among HIV+ women is associated with higher birth weight. Despite the influence of a large cultural effect and poor prenatal behaviors, interventions to improve diet in HIV+ women may help to increase birth weight.